ANALISIS KINERJA LALU-LINTAS TERMINAL BUS MANDALIKA KOTA MATARAM - MATIUS TALA; LALU HARDI WIJAYA; AMINULLAH AMINULLAH (SOSIAL SAINS DAN TEKNOLOGI, 2022)
The purpose of this study is to analyze the traffic performance in the existing conditions around the Mandalika Terminal and analyze the evaluation of the traffic performance around the Mandalika Terminal. This research is a survey research with descriptive statistical approach. The data required is the performance system of the Mandalika Terminal and traffic conditions around the Terminal and data analysis using descriptive statistics.The results of this study indicate that the traffic performance of Mandalika Bus Terminal that incoming vehicles are dominated on weekdays as many as 1,828 vehicles, 820 for light vehicles (LV), 606 for heavy vehicles (HV), 334 for motorcycles (MC), and 68 for vehicles. non-motorized (UM). As for the vehicles passed on Saturday, 1,073 vehicles, 639 light vehicles (LV), 194 heavy vehicles (HV), 210 motorcycles (MC), and 30 non-motorized vehicles (UM).The number of passenger arrivals for one month was 10,642 for AKAP, and 12,914 for AKDP, while departure was 7,985 for AKAP and 6,088 for AKDP. Based on the results of the survey, analysis, and calculations, several conclusions can be drawn regarding the performance around the Mandalika terminal. Based on the survey results, the traffic performance of the Mandalika Bus Terminal is classified as good